Pengembangan Ekonomi Melalui Sektor Pariwisata - Wibowo, Sukarno; Rusmana, Odang; Zuhelfa, Zuhelfa (Politeknik Pariwisata NHI Bandung, 2017)
Tourism sector is one of the activities that have a strategic role in support international economic developmentin the era of globalization. Influence the development of the tourism industy for the development of the region in the vicinity of the attractions, so as to act as leading industries, the sectors that can boost the economy. The existence o fthe tourism sector will be able to create jobs that will boost the income of the people in the tourist areas When associated with economic developrnent with a balanced growth, tourism can be expected to hold a decisive roleandcan be used a cacatalyst to develop ot her sectors of development. Meanwhile, the economic impact pariwista development can have positive or negative. Its positive impactis(1) create jobs; (2) increasing opportunities, (3) increase the income of the people in the tourist area around. While the negative impact on the environment tis the natural, built environment and cultural environment.